The Tumblr porn ban: power imbalances of corporate personhood - Pettis, Ben, author (Colorado State University. Libraries, 2019)
In late 2018, Tumblr announced updates to its Community Guidelines that banned all adult content from the platform. The microblogging platform had historically been an online queer space, known for being an online venue for LGBTQ+ individuals and communities to safely meet, communicate, and explore their identities in ways that may not have been possible in physical settings. Because the new adult content policy was such a radical change from this previous meaning of the platform, Tumblr used corporate personhood to announce the updated community guidelines. By presenting its corporate person as if it were any other user, Tumblr created a false sense of equality and downplayed the inherent power imbalance present in the platforms ability to define itself contrary to the desires of its users. Because this corporate person is necessarily more powerful than the users, it challenges the extent to which social network sites are compatible with prior myths of online communication as free, open, and equalizing. This article analyzes the announcement of Tumblrs updated adult content policy to demonstrate how corporate personhood is used to downplay the power imbalance between a platform and its users, most notably the platforms ability to include and exclude certain members from the community.
219 - Ben Pettis
Corporate personhood in the announcement of the Tumblr porn ban
Department of Communication Studies.
Poster presented as part of the 2019 CSU Graduate Student Showcase.
Keywords: Tumblr; social media; content regulation; adult content